Analisis Efisiensi Pasar Modal “Semistrong Form Tests” dengan adanya pengumuman “Right Issue” di Bursa Efek Jakarta - Gunawan, Barbara (Journal of Accounting and Investment, 2016)
The objective of this study is to find whether Indonesian stock market is a semistrong efficient market. This study use 10 listed public companies in Jakarta Stock Exchange and performed right issue in 2003. The study found there was a significantly difference between stock price at stock exchange and theoretical price before and after ex right date. This study also reveal that abnormal return before and after ex right date does not have a significant different.